The impact of the Corona pandemic (Covid-19) on the disclosure of social responsibility in the financial reports of Libyan commercial banks - جمعة إبراهيم, كريمة; عمر العموري, زينب; أمراجع البركي, وفاء (Dirasat in Economics and Business, 2024)
This study aims to know the level of.social responsibility disclosure concept in the financial reports of companies in light of the Corona pandemic (covid-19), and to achieve this goal the descriptive analytical method was used. Data were collected by means of a questionnaire distributed to the accounting department employees of four Libyan commercial banks, 38 out of 40 questionnaires were analyzed and a One-sample t-test was used, to find out the level of social disclosure. The study concluded that there is a good level of disclosure of the concept of social responsibility in corporate financial reports, during the Corona